Analysis Potential Drug’s Interaction In Prescription Compouded At Arbai Pharmacy From January To March 2024 - Sri Hartini, Indah; Shoviantari, Fenita; Admaja, Wika; Tuna, Hartati; Bhakti Marhenta, Yogi (Pena Medika : Jurnal Kesehatan, 2025)
Prescriptions compounded are prescriptions that have the potential for drug’s interactions. Drug-drug interactions can occur pharmaceutically, pharmacokinetically, and pharmacodynamically. These interactions can cause a decrease in effectiveness, an increase in drug toxicity, resulting in the failure to achieve the expected therapeutic goals. The potential for drug-drug interactions can occur in both compounded and non-compounded prescriptions. Compounded prescriptions are often given to children to adjust the dosage as needed. This study aims to determine the potential for drug-drug interactions in compounded prescriptions at the Arbai Bandar Lor Pharmacy. This study is descriptive and non-experimental. Data collection was conducted retrospectively on compounded prescriptions from January to March 2024 that met the inclusion and exclusion criteria. Determining drug-drug interactions using the Drug Interaction Checker 2024 application Results and conclusions: Pharmaceutically, there were 2 unstable prescriptions (1.90%) and 103 compatible prescriptions (98.10%). The results of the analysis of potential drug-drug interactions were found in 21 prescriptions (20%). The mechanism of interaction was pharmacokinetic in 7 (46.67%) combinations and pharmacodynamic in 8 (53.33%) combinations, with a minor severity level in 4 (26.67%) cases and a moderate severity level in 11 (74.33%) cases, based on the Medscape Drug Interaction Checker reference.